Television drama as central story-telling system in contemporary Italy - Buonanno, Milly (MATRIZes, 2007)
The article will reconstructs the «success story» of end-of-century italian tv fiction, within the context of cultural processes and industrial and regulatory factors that have grounded and supported it. The elements which relate the television story-telling to the italian identity, will be focused; with special reference to the powerful wave of stories which, at the millennium turn, have drawn inspiration and contents from the source of the catholic sentiment and the collective memory of italian population.